2011
DOI: 10.1159/000324113
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy Is Effective and Safe in Patients with Early-Stage Non-Small Cell Lung Cancer with Low Performance Status and Severe Comorbidity

Abstract: Background: The purpose of this study was to assess stereotactic body radiation therapy (SBRT) results and toxicity for stage I non-small cell lung cancer patients with low performance status and severe comorbidity. Patients and Methods: From September 2008 to April 2010, 36 patients with 38 lesions were treated with hypofractionated SBRT. All except one were medically inoperable, had low performance status and/or severe cardiovascular and/or cardiopulmonary comorbidity. The patients were immobilized in an Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Stereotactic body radiation therapy (SBRT) for early stage, single lesion, medically inoperable lung cancer has been extensively studied 13–16 with good success and remains a mainstay treatment option for patients who refuse surgery or are determined to be medically inoperable. Only Sinha and McGarry 17 had previously reviewed the use of SBRT for MPLC and determined the technique to be possibly safe and potentially effective in a previous report.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic body radiation therapy (SBRT) for early stage, single lesion, medically inoperable lung cancer has been extensively studied 13–16 with good success and remains a mainstay treatment option for patients who refuse surgery or are determined to be medically inoperable. Only Sinha and McGarry 17 had previously reviewed the use of SBRT for MPLC and determined the technique to be possibly safe and potentially effective in a previous report.…”
Section: Introductionmentioning
confidence: 99%
“…The results of her study showed that after a median follow-up period of 16.5 months (range: 3.5-40.7), all but 2 patients demonstrated radiological tumor regression. Eight patients (24%) achieved complete remission [12]. Another study conducted by Hualin Zhang and fellow colleagues assessed survival rates for patients recovering from SBRT for liver cancers.…”
Section: Sbrt For Liver Cancersmentioning
confidence: 99%
“…The poor survival rates of ES-NSCLC patients who are medically inoperable and treated with SBRT can be attributed to the fact that this patient population is often older, has multiple severe co-morbidities and a low performance status, as reported in previous studies (4). Although population-based and randomized controlled studies have proven the benefit of SBRT, the extent of this benefit in frail patients is frequently questioned (5,6).…”
Section: Introductionmentioning
confidence: 99%